2019
DOI: 10.1016/j.cell.2018.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic Control of Sebaceous Glands by Innate Lymphoid Cells Regulates Commensal Bacteria Equilibrium

Abstract: SUMMARY Immune cells and epithelium form sophisticated barrier systems in symbiotic relationships with microbiota. Evidence suggests that immune cells can sense microbes through intact barriers, but regulation of microbial commensalism remain largely unexplored. Here, we uncovered spatial compartmentalization of skin-resident innate lymphoid cells (ILCs) and modulation of sebaceous glands by a subset of RORγt+ ILCs residing within hair follicles in close proximity to sebaceous glands. Their persistence in skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
162
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(201 citation statements)
references
References 44 publications
5
162
1
2
Order By: Relevance
“…Another study demonstrated that Id2 expression in ILC3s was important for the generation of IL‐22, which maintained a healthy microbiota that exhibited early colonization resistance to Citrobacter rodentium . ILC3s in the skin were recently shown to control the growth of the sebaceous glands and consequently the release of antimicrobial lipids, enabling the establishment of a healthy skin microbiota …”
Section: Microbiota and Ilc Interactions During Steady‐state In Adultmentioning
confidence: 99%
“…Another study demonstrated that Id2 expression in ILC3s was important for the generation of IL‐22, which maintained a healthy microbiota that exhibited early colonization resistance to Citrobacter rodentium . ILC3s in the skin were recently shown to control the growth of the sebaceous glands and consequently the release of antimicrobial lipids, enabling the establishment of a healthy skin microbiota …”
Section: Microbiota and Ilc Interactions During Steady‐state In Adultmentioning
confidence: 99%
“…Furthermore, sebocytes have an immunomodulatory capacity 27,28 and can produce several lipids and peptides that have demonstrable antimicrobial properties. [29][30][31][32] Loss of these physiological functions of SGs might contribute to the pathogenesis of many skin diseases. 33 To identify the mechanisms that govern pathological processes relevant to acne and other SG-associated dermatoses, it is imperative to understand the mechanisms underlying SG homeostasis.…”
mentioning
confidence: 99%
“…The increase in the size of sebaceous glands and the associated oily-looking fur in TNFdel4 and TNFdel4del5 mice is rather surprising since it was not observed in TNFDARE, BPSM1 and TNFdel4del6 mice. A recent report indicated that sebaceous gland homeostasis was regulated by a population of innate lymphoid cells (ILCs) residing within hair follicles in close proximity to the glands (19). These RORgt+ ILCs were found to negatively regulate sebaceous gland function by expressing TNF and lymphotoxins LTa3 and LTa1b2, which downregulated Notch signaling.…”
Section: Discussionmentioning
confidence: 99%